(untitled) (International Journal of Environmental Sciences, 2025)
Now a day’s voltage instability related problems in power system affects the system constraints and leads to voltage instability. Under normal operating conditions the Voltage instability problem is leads to interruptions in power system and this will reduces the system performance. The power system will require maintaining voltage stability during normal working condition to obtain better performance. It will go into instability state if a large interruption or increase in load requirement, or change in system condition causes a progressive and uncontrollable reduction in voltage. The unmanaged reactive power flow is the main reason for voltage instability in power system. A control of reactive power flow is done by means of Flexible AC Transmission System (FACTS) is a model of modern device. The effective management of reactive power flow is done by introducing FACTS device. The dynamic performance of the power system can be improved by providing automatic FACT Devices. This work deals with voltage instability prevention process in power system with the provision of automatic fact device. The design aims to reduce the voltage instability of power systems by means of providing automatic fact device. The outcome showed that the proposed technique reduced the voltage instability in IEEE system, and this method performed meta-heuristic optimization technique.